2008
DOI: 10.1007/s00702-008-0152-2
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride enhances the anticonvulsant action of various antiepileptic drugs in the mouse maximal electroshock seizure model

Abstract: Accumulating evidence indicates that amiloride (a potassium-sparing diuretic) exerts the anticonvulsant action in various in vivo and in vitro experiments. Therefore, the objective of this study was to assess the influence of amiloride on the protective action of numerous conventional and second-generation antiepileptic drugs [AEDs: carbamazepine (CBZ), lamotrigine (LTG), oxcarbazepine (OXC), phenobarbital (PB), topiramate (TPM), and valproate (VPA)] against maximal electroshock (MES)-induced seizures in mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 47 publications
3
27
0
Order By: Relevance
“…Because inhibitory interneurons in hippocampus display higher ASIC current amplitudes than pyramidal neurons it is possible that the interneuron-mediated inhibition ended the seizures (Ziemann et al, 2008). Observations of seizure inhibition by high concentrations ASIC and ENaC Function and Pharmacology of amiloride (Ali et al, 2006;N'Gouemo, 2008;Luszczki et al, 2009) appear to contradict the role of ASIC1a in seizure termination. Because of its hydrophilic nature, amiloride is expected not to cross the blood-brain barrier, and it is currently not clear whether it reaches the brain or whether it exerts anti-seizure effects by other mechanisms.…”
Section: Tissue Distribution Cellular Functions and Physiologimentioning
confidence: 99%
“…Because inhibitory interneurons in hippocampus display higher ASIC current amplitudes than pyramidal neurons it is possible that the interneuron-mediated inhibition ended the seizures (Ziemann et al, 2008). Observations of seizure inhibition by high concentrations ASIC and ENaC Function and Pharmacology of amiloride (Ali et al, 2006;N'Gouemo, 2008;Luszczki et al, 2009) appear to contradict the role of ASIC1a in seizure termination. Because of its hydrophilic nature, amiloride is expected not to cross the blood-brain barrier, and it is currently not clear whether it reaches the brain or whether it exerts anti-seizure effects by other mechanisms.…”
Section: Tissue Distribution Cellular Functions and Physiologimentioning
confidence: 99%
“…One of them showed that acidsensing ion channel 1a (ASIC1a) activation enhances neuronal excitability in the hippocampus and neocortex, indicating that ASIC1a might play a role in the generation and maintenance of epileptic seizures [292]. Other publication mentioned that ASICs' inhibitor -amiloride neither altered the threshold for electroconvulsions, nor protected the animals against MES-induced seizures in mice but amiloride administered 75 and 100 mg/kg, i.p., 120 min prior to the test significantly enhanced the anticonvulsant effects of carbamazepine, oxcarbamazepine and phenobarbital, by reducing their ED 50 values in the MES test [291]. On the other hand, there was also established that seizures reduce extracellular pH.…”
Section: Epilepsymentioning
confidence: 93%
“…The mice were injected intraperitoneally (i.p.). The doses of drugs were chosen from previous studies (Eraly et al, 2006;Luszczki et al, 2003;Cryan et al, 2004;Kosuda et al, 1997;Hesdorfffer et al, 2001;Mogilnicka et al, 1987).…”
Section: Methodsmentioning
confidence: 99%